2008
DOI: 10.1089/pho.2007.2149
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Action on Dentin Using a Light-Emitting Diode Light Source

Abstract: Objective: The aim of this study was the evaluation of two different photosensitizers activated by red light emitted by light-emitting diodes (LEDs) in the decontamination of carious bovine dentin. Materials and Methods: Fifteen bovine incisors were used to obtain dentin samples which were immersed in brain-heart infusion culture medium supplemented with 1% glucose, 2% sucrose, and 1% young primary culture of Lactobacillus acidophilus 10 8 CFU/mL and Streptococcus mutans 10 8 CFU/mL for caries induction. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 33 publications
6
59
0
11
Order By: Relevance
“…Similar results have been shown in previous studies using different photosensitizers on oral bacteria. [38][39][40][41] One of the main observations made during the first tests to photoinactivate bacteria with conventional photosensitizers was the relative sensitivity of gram-positive strains to photodynamic inactivation. 24 This sensitivity was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been shown in previous studies using different photosensitizers on oral bacteria. [38][39][40][41] One of the main observations made during the first tests to photoinactivate bacteria with conventional photosensitizers was the relative sensitivity of gram-positive strains to photodynamic inactivation. 24 This sensitivity was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, PDT data from previous studies in mutans streptococci are available for a few other photosensitizers, including toluidine blue O [11,12,14,17,18,20], methylene blue [16,19], erythrosine [15,16], hematoporphyrin derivative [16,20], native and lysine-conjugated chlorin e6 [21], aluminium disulphonated or cationic Zn(II) phthalocyanine [22,23], and Rose Bengal [13]. Our results as well as the vast majority of the above published data underlined the usefulness of PDT to destroy mutans streptococci, supporting the general observation that Gram-positive bacteria are susceptible to inactivation by photodynamic procedures [31].…”
Section: Discussionmentioning
confidence: 99%
“…These included tricyclic dyes [11][12][13][14][15][16][17][18][19][20] or tetrapyrroles belonging to the classes of porphyrines [16,20], chlorins [21], and phthalocyanines [22,23]. However, to the best of our knowledge, neither mesotetra(hydroxyphenyl)chlorin (mTHPC) nor hypericin (HYP) had been tested for treatment of S. mutans or S. sobrinus by PDT.…”
Section: Introductionmentioning
confidence: 99%
“…Results of several studies demonstrated an antibacterial effect of PDT on oral bacteria in biofilms [13,14] and in dentine carious lesions [9,[15][16][17][18]. However, none of those studies used curcumin as a PS to kill cariogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%